2004
DOI: 10.1097/00054725-200409000-00014
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal Interleukin-13 in Pediatric Inflammatory Bowel Disease Patients

Abstract: Diminished intestinal IL-13 production is present in UC patients and wanes further with clinical disease progression. These findings suggest that UC patients may be differentiated from CD patients by intestinal IL-13 quantitation, and UC patients may benefit from IL-13 enhancing therapies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 23 publications
2
28
0
1
Order By: Relevance
“…This study also showed up-regulated mucosal TLR4 expression in patients with ulcerative colitis, which has recently been linked to atypical mucosal IL-13 expression (28,37). However, other studies described different mucosal Th cytokine profiles in patients with ulcerative colitis, ranging from diminished mucosal IL-13 expression (38,39) to increased IL-5 expression (40).…”
Section: Discussionsupporting
confidence: 59%
“…This study also showed up-regulated mucosal TLR4 expression in patients with ulcerative colitis, which has recently been linked to atypical mucosal IL-13 expression (28,37). However, other studies described different mucosal Th cytokine profiles in patients with ulcerative colitis, ranging from diminished mucosal IL-13 expression (38,39) to increased IL-5 expression (40).…”
Section: Discussionsupporting
confidence: 59%
“…In our experiments however, the addition of rhIL-13 to unstimulated or anti-CD3/CD28-stimulated LPMCs from inflamed UC did not have any influence on their production of classical pro-inflammatory cytokines such as TNF-α, IFN-γ and IL-17A. The concentration of rhIL-13 that we used in our experiments (20 ng/mL) is tenfold higher than that reported to induce changes in epithelial permeability, and the same described to exert pro-fibrogenic effects, so we have no doubt that we added biologically active doses to the LPMCs [15,27], and this is confirmed by the up-regulation of claudin 2 expression induced by rhIL-13 in T84 cells. Since IL-13 and TNF-α can exert a synergistic effect on the expression of IL-13Rα2 and TNF-α has a known pro-fibrogenic action [17], we finally tested the effect of exogenous rhIL-13 and/or rhTNF-α on submucosal myofibroblasts isolated from CD strictures and control gut.…”
Section: Discussionmentioning
confidence: 67%
“…Our data suggest that claudin 2 was more highly expressed in UC (see Figure 4, Table 2) and it has recently been reported that mucosal T cells from UC patients make more IL-13 than T cells from normal patients or CD. 38 We hesitate to suggest that IL-13 is one of the mechanistic drivers of altered claudin 2 expression in IBD since the current literature on levels of IL-13 in IBD is contentious with studies showing both increased 38 and decreased levels 98,99 in disease. Our data from a cell culture model of the epithelial barrier indicate that one consequence of increased IL-13 would be to increase permeability, potentially involving increased claudin 2 expression, and that inflammatory cytokines may alter tight junctions via differential effects on claudin proteins.…”
Section: Inflammatory Cytokines and Claudin Expression S Prasad Et Almentioning
confidence: 99%